Synthesis and characterization of structural and optical properties of heteroepitaxial brookite TiO2 single crystalline films. (1st April 2016) - Wang, Weiguang; Wang, Mingxian; Li, Zhao; Du, Xuejian; Xu, Haisheng; Zhao, Wei; Feng, Xianjin; Ma, Jin
Abstract: Brookite titanium dioxide (b-TiO2 ) films were successfully deposited on Y-stabilized ZrO2 (110) substrates at different substrate temperatures (500–650 °C) by the metal organic chemical vapor deposition technique. The results of X-ray diffraction θ-2θ scan indicated that the b-TiO2 film deposited at 550 °C had the best single crystalline quality, for which the heteroepitaxial relationship and the microstructure were identified by the X-ray diffraction Φ scan and high resolution transmission electron microscopy measurements. A schematic diagram was proposed to clarify the epitaxial growth mechanism. The composition, morphology and optical properties of the b-TiO2 films have been investigated in detail. Graphical abstract: